KEMAMPUAN LITERASI BIOLOGI BERDASARKAN GENDER PADA SISWA PEMINATAN MIPA DI SMA NEGERI KABUPAEN LOMBOK BARAT - Erni Zuhara; A. Wahab Jufri; Harry Soeprianto (Postgraduate, University of Mataram, 2019)
PISA measurement results from 2000-2015 show the fact that students in Indonesia have a low ability in the science literacy. This study aims to determine the ability of biological literacy based on gender in MIPA Specialization students in SMA Negeri in West Lombok regency. This research used descriptive qualitative method. Samples of research were 360 students from 2357 students of class XI and XII MIPA interest in 6 Senior High Schools of West Lombok regency in learning year 2017/2018. The research instrument uses adaptation of PISA Science Literacy test in 2006 and 2009 which consists of two aspects, namely: Knowledge and Competency). The result of this research: Biology literacy ability of MIPA Student by gender in West Lombok regency, male students dominant at level 1, level 2 and level 3 while female student is dominant at level 4, level 5 and level 6.Keywords: Biological literacy, Gender, MIPA Specialization